java.rmi: The Remote Method Invocation Guide - Pitt, Esmond; McNiff, Kathleen (Pearson Business, 2001)
"This book collects an astonishing range of Java RMI material, suitable for any Java programmer regardless of experience with RMI. The RMI novice will be able to run RMI programs without excessive hair-pulling; the accomplished RMI programmer will find enough techniques and explanations to improve the performance, capability, or aesthetic quality of his or her code; and the RMI expert will be able to perform great RMI-based hacks without the JDK source code. If you're looking at this book because I directed you to it on the RMI-USERS mailing list, then, yes, you've found the right one!" --from the foreword by Adrian Colley, RMI team, Sun Microsystems, Ireland "Esmond is one of the long-time RMI 'gurus', accumulating a vast and deep arsenal of practical knowledge in RMI uses, internals, tricks and techniques. I am amazed he has packed so much in just under 300 pages. An effective RMI or Jini developer should absolutely have this reference in his collection." --Brian Maso; consultant, DevelopMentor instructor, and Java Pro at DevX.com" The definitive guide to remote method invocation in Java. This book provides an in-depth resource to all features of RMI, building a firm, logical foundation for understanding and applying the RMI technology. It contains detailed information about how to apply RMI to get professional developers and students alike "up and running", while clarifying and extending the official information found in the specification. The authors address many of the real-world issues and unexpected features that you will encounter whilst working with the technology. All you need to know about: understanding RMI in the context of Java and object-oriented programming using RMI to create applications in networked environments ranging from LANs to the Internet mastering serialization, remote interfaces, clients, the RMI registry, servers, security, and mobile code applying advanced concepts e.g. activation, socket factories, Internet firewalls, distributed garbage collection, and design patterns working with alternatives or extensions to the standard RMI implementation e.g., JNDI naming services and CORBA IIOP. Features: Complete RMI Alamanac lift-out Extensive code samples and exercises 0201700433B07022001.